A phenomenological study on understanding of mothers' knowledge on breast feeding practices in Malaysia - Jamil, Nurul Akma; Muda, Siti Mariam; Aung, Khin Thandar (2017)
Realizing the importance of children’s nutrition, the World Health Organization strive vast effort to ensure revitalize promotion and protection of infant and young child feeding. Despite its benefits, the breastfeeding rate was still low worldwide including Malaysia. Based upon the findings of the scientific research, it was expected to contribute significant effects on people’s knowledge and perception towards breastfeeding practice. In Malaysia, breastfeeding was found to be dominantly practiced among Malay. The qualitative study design was used to explore Malay mother’s knowledge on the benefits of breastfeeding towards maternal and infant’s health. Fifteen mothers who currently breastfeed their children were recruited by purposive sampling method for this study. Data were collected by in-depth interview using a semi-structured interview guide. Data obtained were analyzed using thematic analysis. Due to study findings, mothers were aware on the nutritional and protective factors contain in breast milk. However, the misperception on colostrum still exists and it was conveyed by influential people in mothers’ life. Mothers perceived breastfeeding could help in maintaining their appearance following child birth. It protects mothers by minimizing the risk of postpartum haemorrhage and incidence of breast cancer. Mothers in this study recognized breastfeeding as a form of birth control. Even so, they doubted on its effectiveness because of lack of understanding on the mechanism of lactation amenorrhea. Social media, health care professionals particularly staff nurses, and breastfeeding support group were the first three most cited source of information by the mothers in this study. According to culture and religious in Malaysia, family greatly support to breast feeding mothers during their breast-feeding period. However, continuing of the breast feeding depends on mother’s knowledge and decision. Therefore, as the health care providers, especially nurses who are closely with mothers keeps on giving health education regarding breast feeding practice to enhance their knowledge and understanding.